All Days 1987
DOI: 10.2118/16344-ms
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Advance Theory for Flow in Heterogeneous Porous Media

Abstract: SPE Members Abstract This paper concerns the application of frontal advance theory to displacement processes in heterogeneous porous media. The assumptions under which a generalized frontal advance equation can be used to describe a flow process in a heterogeneous porous medium are examined, Material balance equations are derived based on these assumptions, and the theory is illustrated by application to the Dykstra-Parsons model of flow in noncommunicating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The WL method treats the SWAG injections as a combination of the miscible waves (gas/oil) and immiscible waves (water-oil/solvent) propagating according to the given initial and injection conditions. On the other hand, previous studies by Pande et al (1987), Sorbie et al (1994), and Li and Lake (1995) showed that a linear growth of the mixing zone with time will be observed if the simulation results are consistent with the fractional-flow solutions. Therefore, a similar behavior is expected for SWAG displacements when the WL solution is accurate.…”
Section: Development Of the Mixing Zone With Timementioning
confidence: 66%
See 1 more Smart Citation
“…The WL method treats the SWAG injections as a combination of the miscible waves (gas/oil) and immiscible waves (water-oil/solvent) propagating according to the given initial and injection conditions. On the other hand, previous studies by Pande et al (1987), Sorbie et al (1994), and Li and Lake (1995) showed that a linear growth of the mixing zone with time will be observed if the simulation results are consistent with the fractional-flow solutions. Therefore, a similar behavior is expected for SWAG displacements when the WL solution is accurate.…”
Section: Development Of the Mixing Zone With Timementioning
confidence: 66%
“…Helfferich (1981) introduced the general theory of multicomponent and multiphase flow in permeable media by incorporating the theories of multi-component chromatography and fractional flow. Pande et al (1987) showed that the 1D fractional-flow solution of immiscible displacements can be used to qualitatively reproduce the displacement performance of 2D flow with noncommunicating layers.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore clear that extending the frontal advance theory in the sense of BL displacement to stratified systems is only valid for communicating systems with complete crossflow between layers. Pande et al 12 tried to extend this theory using the DP model ͑noncommunicating͒ but found agreement only for unit mobility ratio. At other mobility ratios, the velocities of the individual saturations were not constant with time as would be expected from Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Such parameters can also be used with simple models to compute displacement performance. 27 It is obvious that when the scale of heterogeneities is comparable to system dimensions, the tracer flow response strongly depends on the exact arrangement of permeability in the flow field. Thus, even when average measures (variance and correlation length scale) of permeability variation are the same, tracer flow behavior (as well as the recovery behavior from an EOR process) might be completely different.…”
Section: Simulation Of Tracer Flowmentioning
confidence: 99%